Carbonized MOF negative electrode modified material and preparation method and application thereof
By using carbonized MOF negative electrode modified materials on the negative electrode of lithium metal batteries, the problems of dendrite growth and Coulombic efficiency during the cycle process are solved, and higher battery safety performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202510106792.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-15
AI Technical Summary
Lithium metal batteries have problems such as dendrite growth and low Coulomb efficiency during circulation, and lithium metal is prone to volume changes and dendrite growth during electroplating and peeling, resulting in a decline in battery performance and an increase in safety risks.
Using a carbonized MOF negative electrode modified material, bimetal MOF is obtained by mixing the mixed metal salt solution and imidazole ligands to precipitate, and then carbonized at high temperature in an inert gas environment to obtain a carbonized MOF modified material, which is dispersed in an organic solvent and added dropwise to the surface of the lithium foil to form a carbonized MOF negative electrode modified material.
The modified materials improve the safety performance and cycle stability of lithium metal batteries, avoid dendrites, enhance the affinity of electrolytes, promote the transmission of ions and electrons, and improve the energy density and coulomb efficiency of the battery.
Smart Images

Figure CN119822359A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium metal batteries, and in particular relates to a carbonized MOF negative electrode modified material and a preparation method and application thereof Background Art
[0002] As a high energy density energy storage technology, lithium metal batteries have received extensive attention and research in recent years. Lithium metal batteries are chemical power sources with lithium metal as the negative electrode. They have high theoretical capacity and low electrochemical potential, so they are considered to be an ideal choice for achieving high energy density energy storage. However, the decomposition of liquid electrolytes will promote the formation of SEI, and the properties of SEI directly affect the reversibility of the lithium metal negative electrode and the performance of the battery. The formation process of SEI is complex and difficult to control, which can easily lead to problems such as pulverization and dendrite growth of the lithium metal negative electrode. Moreover, lithium metal is prone to volume changes and dendrite growth during electroplating and stripping, resulting in decreased battery performance and increased safety risks. In recent years, with the continuous deepening of research on lithium metal batteries, many important research advances have been made. For example, the performance and safety of lithium metal batteries have been improved by optimizing electrolyte design and SEI engineering; the reversibility and cycle stability of lithium metal negative electrodes have been improved by developing new lithium metal negative electrode materials and optimizing deposition / stripping processes. At present, the research on lithium metal batteries focuses more on the development of high-performance electrolyte materials, the optimization of SEI stabilization mechanism, and the innovative design of lithium metal negative electrode materials. Lithium negative electrode modification has not yet paid attention to the transmission of ions and electrons on lithium metal to promote redox reactions and increase the energy density of lithium batteries. Therefore, it is very necessary to propose a method that can add a modified material to lithium metal to promote ion and electron transmission and is simple to use and low in cost. Summary of the invention
[0003] The present invention provides a method for preparing a carbonized MOF negative electrode modified material. The prepared carbonized MOF negative electrode modified material can modify lithium metal at a low cost, solve the problems of dendrite growth and low coulombic efficiency in the existing lithium metal negative electrode during the cycle process, promote ion and electron transmission, and improve the safety performance of lithium metal batteries.
[0004] To achieve the above object, the present invention provides a method for preparing a carbonized MOF negative electrode modified material, comprising the following steps:
[0005] S1. adding a mixed metal salt solution and an imidazole ligand into a co-solvent and stirring to obtain a mixed solution, centrifuging and washing the precipitate after standing and settling to obtain a bimetallic MOF, wherein the mixed metal salt includes a zinc salt and at least one other metal salt, and the metal in the other metal salt can catalyze graphitization of amorphous carbon at high temperature;
[0006] S2. In an inert gas environment, the bimetallic MOF obtained in step S1 is carbonized at a high temperature in an inert atmosphere to obtain a carbonized MOF modified material, wherein the carbonization temperature is 400 to 600° C.;
[0007] S3. In an inert gas environment, the carbonized MOF modified material is dispersed in an organic solvent, stirred and allowed to stand, and then the mixed solution is evenly dropped on the surface of the lithium foil to obtain the carbonized MOF negative electrode modified material.
[0008] In step S1
[0009] The metal in the other metal salts is selected from at least one of Fe, Mn, Co, Ni, and Cu. The molar ratio of the zinc salt to the Ni metal salt is 1:0.98-2.21, the molar ratio of the zinc salt to the Fe metal salt is 1:0.55-1.65, the molar ratio of the zinc salt to the Mn metal salt is 1:1.5-3.00, the molar ratio of the zinc salt to the Cu metal salt is 1:2.27-4.01, and the molar ratio of the zinc salt to the Co metal salt is 1:0.98-2.21.
[0010] The imidazole ligand includes at least one of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-nitroimidazole and benzimidazole;
[0011] The co-solvent is selected from one or more of water, methanol, ethanol, acetone and dimethylformamide.
[0012] The molar ratio of the zinc salt to the imidazole ligand in step S1 is 1:14.49-21.73, and the concentration of the mixed solution is 0.5 mg / ml-2 mg / ml.
[0013] In the step S1, the stirring time is 3h-5h, the static sedimentation time is 12-24h, and the centrifugation is carried out at a speed of 8000-14000rpm.
[0014] During the high-temperature carbonization in step S2, the heating rate is 2°C / min-4°C / min, the heating range is 400°C-800°C, and the carbonization insulation time is 2h-6h; the transition metal complex needs to be fully ground in agate mortar before high-temperature sintering for 40-60min.
[0015] In step S3, the organic solvent is at least one of DME, DOL, EC, and DEC, the concentration of the carbonized MOF modified material is 0.01-0.05 mg / ml; the stirring time is 12-24 hours, the standing time is 12-24 hours; and the volume of the lithium foil is 10 μl to 150 μl.
[0016] A carbonized MOF negative electrode modified material prepared by the preparation method of the carbonized MOF negative electrode modified material, the carbonized MOF negative electrode modified material comprises a lithium foil and a carbonized MOF coating layer on the surface of the lithium foil, the pore size of the modified material is 0.5nm to 1nm, the particle size is 100nm to 500nm, and the specific surface area is 100m 2 / g to 200m 2 / g.
[0017] A negative electrode plate comprises the carbonized MOF negative electrode modified material.
[0018] A lithium ion battery comprises the negative electrode plate.
[0019] Beneficial effects: The present invention proposes a carbonized MOF negative electrode modification material, which is used in lithium metal batteries, and the carbonized MOF material is dripped on lithium foil. Compared with unmodified lithium foil, the modified lithium foil has better electrolyte affinity due to the introduction of carbonized MOF modification material, and can well desolvate ions; in addition, the MOF modified material contains abundant lithium-philic elements and nanopores, among which the lithium-philic elements can reduce the migration energy barrier of lithium ions, and the nanopores can homogenize the flow of lithium ions, and have high ion conductivity; due to the effect of carbonization, the electronic conductivity of the lithium foil surface can be significantly enhanced, and the composition of the beneficial components of the SEI film is greatly enhanced, so that the ion-electron double conductive layer is constructed; under the synergistic effect, the lithium metal negative electrode can achieve a uniform deposition and stripping process, thereby avoiding the growth of lithium dendrites, and having little effect on the energy density of the battery. The metal lithium battery based on this modified lithium foil shows good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a scanning electron microscope image of the modified lithium foil in Example 1;
[0021] Figure 2 This is the XPS spectrum of the electrode surface of the modified lithium foil in Example 1 after battery cycling;
[0022] Figure 3 is the Raman spectrum of Example 1;
[0023] Figure 4 The impedance comparison diagram of Example 1 and Comparative Example 1;
[0024] Figure 5 is a scanning electron microscope image of the modified lithium foil in Example 2;
[0025] Figure 6 is a scanning electron microscope image of the modified lithium foil in Example 3;
[0026] Figure 7This is a scanning electron microscope image of the modified lithium foil in Example 4. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is described below through specific embodiments.
[0028] In the term "1M LiTFSIDOL / DME", 1M means the concentration is 1 mole per liter, LiTFSI is a lithium salt, DOL, DME, EC and DEC are organic solvents, DOL is dioxolane, DME is dimethyl ether, EC refers to ethylene carbonate, and DEC is diethyl carbonate, all of which have a higher dielectric constant and a lower viscosity, which helps to improve the ionic conductivity and electrochemical stability of the electrolyte.
[0029] The commercial lithium foil is pretreated before modification by polishing with sandpaper and then drying for use.
[0030] Example 1
[0031] A method for preparing a carbonized MOF negative electrode modified material comprises the following steps:
[0032] (1) Zinc nitrate hexahydrate, nickel chloride hexahydrate and 2-methylimidazole were added to a beaker in a mass ratio of 1:1.3:4, and mixed with deionized water to form a solution with a total solute concentration of 1 mg / ml. The mixture was then stirred for two hours, and the obtained mixed solution was allowed to settle for 10-12 hours to obtain an impure white precipitate, which was then repeatedly washed three times with anhydrous ethanol and deionized water, and centrifuged at 8000-12000 rpm to obtain an intermediate product, i.e. a white solid precipitate.
[0033] (2) Under argon environment, the white solid precipitate is carbonized at high temperature in a tubular furnace, the temperature is raised to 600°C at a rate of 2°C / min, and then kept warm for 4 hours to obtain a carbonized MOF material. Carbonizing the MOF material at 600°C can both carbonize the MOF and retain the metal elements.
[0034] (3) Under argon environment protection, the obtained carbonized MOF material was mixed with an organic solvent DME, stirred for 12 hours and then allowed to stand. The concentration of the obtained mixed solution containing the carbonized MOF material was 0.01 mg / ml. Subsequently, a pipette was used to drip 50 μl of the mixed solution containing the carbonized MOF material onto the polished lithium foil surface to obtain a carbonized MOF negative electrode modified material.
[0035] Example 2
[0036] The experimental steps are the same as those in Example 1, except that in this example, zinc nitrate hexahydrate, nickel chloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.3:6.
[0037] Example 3
[0038] The experimental steps are the same as those in Example 1, except that in this example, zinc nitrate hexahydrate, nickel chloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.8:4.
[0039] Example 4
[0040] The experimental steps are the same as those in Example 1, except that in this example, zinc nitrate hexahydrate, nickel chloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:0.8:4.
[0041] Example 5
[0042] The experimental steps are the same as those in Example 1, except that nickel chloride hexahydrate is replaced by ferric chloride hexahydrate. In this example, zinc nitrate hexahydrate, ferric chloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1:4.
[0043] Example 6
[0044] The experimental steps are the same as those in Example 5, except that in this example, zinc nitrate hexahydrate, ferric chloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1:6.
[0045] Example 7
[0046] The experimental steps are the same as those in Example 5, except that in this example, zinc nitrate hexahydrate, ferric chloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.5:4.
[0047] Example 8
[0048] The experimental steps are the same as those in Example 5, except that in this example, zinc nitrate hexahydrate, ferric chloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:0.5:4.
[0049] Example 9
[0050] The experimental steps are the same as those in Example 1, except that nickel chloride hexahydrate is replaced by manganese chloride tetrahydrate. In this example, zinc nitrate hexahydrate, manganese dichloride tetrahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.5:4.
[0051] Example 10
[0052] The experimental steps are the same as those of Example 9, except that in this example, zinc nitrate hexahydrate, manganese dichloride tetrahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.5:6.
[0053] Embodiment 11
[0054] The experimental steps are the same as those of Example 9, except that in this example, zinc nitrate hexahydrate, manganese dichloride tetrahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1:4.
[0055] Example 12
[0056] The experimental steps are the same as those of Example 9, except that in this example, zinc nitrate hexahydrate, manganese dichloride tetrahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:2:4.
[0057] Example 13
[0058] The experimental steps are the same as those in Example 1, except that nickel chloride hexahydrate is replaced by cupric chloride dihydrate. In this example, zinc nitrate hexahydrate, cupric chloride dihydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.8:4.
[0059] Embodiment 14
[0060] The experimental steps are the same as those of Example 13, except that in this example, zinc nitrate hexahydrate, cupric chloride dihydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.8:6.
[0061] Embodiment 15
[0062] The experimental steps are the same as those of Example 13, except that in this example, zinc nitrate hexahydrate, cupric chloride dihydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.3:4.
[0063] Example 16
[0064] The experimental steps are the same as those of Example 13, except that in this example, zinc nitrate hexahydrate, cupric chloride dihydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:2.3:4.
[0065] Embodiment 17
[0066] The experimental steps are the same as those in Example 1, except that nickel chloride hexahydrate is replaced by cobalt chloride hexahydrate. In this example, zinc nitrate hexahydrate, cobalt dichloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.3:4.
[0067] Embodiment 18
[0068] The experimental steps are the same as those in Example 17, except that in this example, zinc nitrate hexahydrate, cobalt dichloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.3:6.
[0069] Embodiment 19
[0070] The experimental steps are the same as those of Example 17, except that in this example, zinc nitrate hexahydrate, cobalt dichloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:1.8:4.
[0071] Embodiment 20
[0072] The experimental steps are the same as those of Example 17, except that in this example, zinc nitrate hexahydrate, cobalt dichloride hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:0.8:6.
[0073] Embodiment 21
[0074] The experimental steps are the same as those in Example 1, except that in this example, zinc nitrate hexahydrate and 2-methylimidazole are respectively taken in a mass ratio of 1:2.
[0075] Comparative Example 1
[0076] Pure lithium foil.
[0077] Figure 1 This is a scanning electron microscope image of the modified lithium foil in Example 1. It can be clearly seen from the scanning electron microscope image that the carbonized MOF material is uniformly introduced into the surface of the lithium foil and presents a coral-like shape with a large specific surface area, which can significantly reduce the interface current density.
[0078] Figure 2 This is the XPS spectrum of the electrode surface of the modified lithium foil after battery cycling in Example 1. It can be clearly seen from the XPS spectrum that Zn and Ni elements exist on the surface of the lithium foil. Zn2p 3 / 2 and Ni2p 3 / 2 represent Zn Ni metallic peaks, indicating the presence of Li-Zn Li-Ni. The introduction of inorganic metal phases enhances the mechanical strength and ion transport of the SEI film.
[0079] Figure 3 The Raman spectrum of Example 1 shows obvious D / G peaks. These two peaks are common characteristic peaks in the Raman spectrum of carbon materials. The surface carbonized material contains a certain degree of graphitized carbon, and also has some defects or disordered structures, which have obvious characteristics of MOF materials.
[0080] Figure 4 The impedance spectra of Example 1 and Comparative Example 1 show that Example 1 has smaller interface transfer impedance and diffusion impedance, indicating that the carbonized MOF modified lithium foil improves molecular dynamics.
[0081] Figure 5 This is a scanning electron microscope image of the modified lithium foil in Example 2. It can be clearly seen from the scanning electron microscope image that due to the addition of too much imidazole, the morphology has changed to a certain extent. The carbonized MOF material is evenly introduced into the surface of the lithium foil and presents an irregular concave-convex structure. The performance decreases with the increase of imidazole.
[0082] Figure 6This is a scanning electron microscope image of the modified lithium foil in Example 3. It can be clearly seen from the scanning electron microscope image that due to the addition of excessive nickel salt, the morphology has changed to a certain extent. The carbonized MOF material is evenly introduced onto the surface of the lithium foil and presents an irregular flaky structure. The performance decreases with the increase of nickel salt.
[0083] Figure 7 This is a scanning electron microscope image of the modified lithium foil in Example 4. It can be clearly seen from the scanning electron microscope image that due to the addition of too little nickel salt, the morphology has changed to a certain extent. The carbonized MOF material is evenly introduced onto the surface of the lithium foil and presents an irregular flaky and irregular concave-convex morphology structure. The performance decreases with the reduction of nickel salt.
[0084] The lithium foils of Examples 1 to 20, Example 21, and Comparative Example 1 were used as the positive and negative electrodes of the battery, the separator was a traditional PP separator, and the electrolyte was an ether ester electrolyte. A symmetrical battery was assembled and tested using a Swiss Metrohm electrochemical workstation to test the ionic conductivity of the battery, and a four-probe tester was used to test the electronic conductivity of the carbonized MOF. The test results are shown in Table 1.
[0085] Table 1
[0086]
[0087]
[0088] Ion mobility is used to evaluate the ability of ion migration. Low ion mobility will not only reduce the ionic conductivity of the electrolyte, but also cause serious concentration polarization, resulting in uneven deposition of lithium ions and affecting the performance of the battery. Good electronic conductivity can enhance the conduction of electrons and contribute to the rapid deposition and stripping of lithium. In addition, whether it can fully contact with the electrolyte also reflects the affinity of lithium metal to the electrolyte, which is related to the interface affinity. It can be seen from Table 1 that the modified composite lithium foil material prepared by mixing and carbonizing a variety of metal salts in Examples 1 to 21 has significant advantages in ionic conductivity, and the electronic conductivity of the carbonized material itself is also improved. The composite lithium foil has a smaller electrolyte contact angle, which is beneficial to reducing the interface impedance.
[0089] Therefore, the present invention preferably uses a mass ratio of zinc nitrate hexahydrate to nickel chloride hexahydrate of 1:1.3.
[0090] Zinc nitrate hexahydrate and ferric chloride hexahydrate: The mass ratio of zinc nitrate hexahydrate to ferric chloride hexahydrate is 1:1.
[0091] Zinc nitrate hexahydrate and manganese chloride tetrahydrate: The mass ratio of zinc nitrate hexahydrate to manganese chloride tetrahydrate is 1:1.5
[0092] Zinc nitrate hexahydrate and cupric chloride dihydrate: The mass ratio of zinc nitrate hexahydrate to cupric chloride dihydrate is 1:1.8.
[0093] Zinc nitrate hexahydrate and cobalt chloride hexahydrate: the mass ratio of zinc nitrate hexahydrate to cobalt chloride hexahydrate is 1:1.3.
[0094] Example 22 This example tests the cycle performance of NCM811 batteries based on different separators.
[0095] Using lithium metal as the negative electrode, NCM811 as the positive electrode, 1M LiPF6 EC / DEC (volume ratio of 1:1) as the electrolyte, and two different separators, NCM811 batteries were assembled in an argon atmosphere glove box.
[0096] The preparation method of the positive electrode sheet is as follows: nickel cobalt manganese (NCM), (conductive carbon black) SuperP, and polyvinylidene fluoride (PVDF) binder are mixed in a mass ratio of 8:1:1, ground evenly and dispersed in polymethylpyrrolidone (NMP), and then placed in a homogenizer for 20 minutes to obtain a uniform slurry, and the slurry is scraped onto aluminum foil with a preparation device and placed in a vacuum drying oven at 80°C for 12 hours.
[0097] Then, taking the CR2025 button battery as an example, the battery was assembled in the order of negative electrode shell, lithium sheet, dripping electrolyte, diaphragm, dripping electrolyte, positive electrode sheet, gasket, and shrapnel, and the battery pressure was 0.85 MPa.
[0098] Table 2 shows the performance of the Li-NCM811 battery in Example 22 after 100 cycles at 0.5C rate. The battery with the composite negative electrode prepared using carbonized MOF modified materials has significantly higher cycle stability than the battery using commercial separators. The high capacity retention rate indicates that the internal interface impedance of the battery is small, which is conducive to the insertion and extraction of ions. The high average coulombic efficiency indicates the utilization rate of lithium ions and the inhibition of the generation of dendrites and dead lithium.
[0099] Table 2
[0100] Diaphragm type Number of cycles Capacity retention rate Average Coulombic efficiency Comparative Example 1 50 54.34% 93.26% Example 1 100 85.23% 99.61% Example 2 100 75.62% 98.43% Example 3 100 73.85% 98.28% Example 4 100 76.53% 98.32% Example 5 100 86.54% 99.53% Example 6 100 74.52% 98.19% Example 7 100 74.22% 98.54% Example 8 100 75.34% 98.32% Example 9 100 85.39% 98.62% Example 10 100 74.65% 98.52% Embodiment 11 100 74.32% 98.43% Example 12 100 75.21% 98.51% Example 13 100 84.99% 99.15% Embodiment 14 100 74.45% 98.42% Embodiment 15 100 75.45% 98.51% Example 16 100 73.49% 98.22% Embodiment 17 100 85.34% 99.21% Embodiment 18 100 75.51% 98.52% Embodiment 19 100 74.36% 98.41% Embodiment 20 100 74.76% 98.39% Embodiment 21 100 78.69% 98.61%
[0101] Zn and Ni ions exhibit different functions during the carbonization process. 2-Methylimidazole coordinated with Zn ions can be converted into nitrogen-doped carbon. During the carbonization process, 2-Methylimidazole from bimetallic ZIF is converted into carbon state, and the coexisting Zn 2+ and Ni 2+The ions are thermally reduced to metallic Zn and Ni nanoparticles, respectively. Incorporation of catalytically active transition metals into carbon precursors (e.g., Fe, Ni, Co, Mn, Cu) has been shown to be an effective method for catalyzing the graphitization of amorphous carbon via solid-state conversion processes. Therefore, 2-methylimidazole surrounding Ni ions tends to be catalytically converted into graphitic carbon, while Zn nanoparticles evaporate during high-temperature treatment, 2-methylimidazole surrounding Zn ions produces amorphous carbon, and Zn volatilizes out of the amorphous carbon to form nanoporous carbon, which usually has a mesoporous structure. The influence of Zn and Ni on the graphitization degree, pore size distribution and nitrogen doping of nanoporous carbon structure. With the increase of Zn content in MOF material, the microporous structure of MOF material after carbonization increases, which is beneficial to increase the specific surface area and improve the contact angle of electrolyte, and is expected to promote electrolyte penetration and reduce diffusion resistance. Nanopores can homogenize the flow of lithium ions and have high ionic conductivity. However, with the increase of Zn content in MOF material, the degree of graphitization decreases, and the electronic conductivity of the lithium foil surface decreases. The nitrogen content in MOF material after carbonization increases with the increase of Zn content. It may be because Ni nanoparticles promote the destruction of CN bonds in the catalytic graphitization process. Nitrogen doping can increase the active sites of graphite layer, improve the efficiency of lithium ion embedding and extraction, provide more lithium ion transmission channels, reduce the diffusion resistance of lithium ions, and thus improve the rate performance of battery. Compared with unmodified lithium foil, the modified lithium foil has enhanced the mechanical strength of the SEI membrane and the ion transport performance due to the introduction of inorganic metal phase by carbonization. The modified lithium foil has better electrolyte affinity. The porous structure of the carbonized MOF layer can adsorb more electrolyte, promote the homogenized ion transport, reduce the interface impedance, and thus promote the desolvation of ions.
[0102] It should be understood that the above description of the preferred embodiment is relatively detailed and cannot be regarded as limiting the scope of patent protection of the present invention. Under the enlightenment of the present invention, ordinary technicians in this field can also make substitutions or modifications without departing from the scope of protection of the claims of the present invention, which all fall within the scope of protection of the present invention. The scope of protection requested for the present invention shall be based on the attached claims.
Claims
1. A method for preparing a carbonized MOF negative electrode modified material, characterized in that: The following steps are involved: S1. adding a mixed metal salt solution and an imidazole ligand into a co-solvent and stirring to obtain a mixed solution, centrifuging and washing the precipitate after standing and settling to obtain a bimetallic MOF, wherein the mixed metal salt includes a zinc salt and at least one other metal salt, and the metal in the other metal salt can catalyze graphitization of amorphous carbon at high temperature; S2. In an inert gas environment, the bimetallic MOF obtained in step S1 is carbonized at a high temperature in an inert atmosphere to obtain a carbonized MOF modified material, wherein the carbonization temperature is 400 to 600° C.; S3. In an inert gas environment, the carbonized MOF modified material is dispersed in an organic solvent, stirred and allowed to stand, and then the mixed solution is evenly dropped on the surface of the lithium foil to obtain the carbonized MOF negative electrode modified material.
2. The preparation method according to claim 1, characterized in that: In the step S1, The metal in the other metal salts is selected from at least one of Fe, Mn, Co, Ni, and Cu. The molar ratio of the zinc salt to the Ni metal salt is 1:0.98-2.21, the molar ratio of the zinc salt to the Fe metal salt is 1:0.55-1.65, the molar ratio of the zinc salt to the Mn metal salt is 1:1.5-3.00, the molar ratio of the zinc salt to the Cu metal salt is 1:2.27-4.01, and the molar ratio of the zinc salt to the Co metal salt is 1:0.98-2.
21. The imidazole ligand includes at least one of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-nitroimidazole and benzimidazole; The co-solvent is selected from one or more of water, methanol, ethanol, acetone and dimethylformamide.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the zinc salt to the imidazole ligand in step S1 is 1:14.49-21.73, and the concentration of the mixed solution is 0.5 mg / ml-2 mg / ml.
4. The preparation method according to claim 1, characterized in that: In the step S1, the stirring time is 3h-5h, the static sedimentation time is 12-24h, and the centrifugation is carried out at a speed of 8000-14000rpm.
5. The preparation method according to claim 1, characterized in that: During the high-temperature carbonization in step S2, the heating rate is 2°C / min-4°C / min, the heating range is 400°C-800°C, and the carbonization insulation time is 2h-6h; the transition metal complex needs to be fully ground in agate mortar before high-temperature sintering for 40-60min.
6. The preparation method according to claim 1, characterized in that: In step S3, the organic solvent is at least one of DME, DOL, EC, and DEC, the concentration of the carbonized MOF modified material is 0.01-0.05 mg / ml; the stirring time is 12-24 hours, the standing time is 12-24 hours; and the volume of the lithium foil is 10 μl to 150 μl.
7. A carbonized MOF negative electrode modified material obtained by the method for preparing a carbonized MOF negative electrode modified material according to any one of claims 1 to 6, characterized in that: The carbonized MOF negative electrode modification material comprises a lithium foil and a carbonized MOF modification material coating layer on the surface of the lithium foil. The carbonized MOF modification material has a pore size of 0.5 nm to 1 nm, a particle size of 100 nm to 500 nm, and a specific surface area of 100 m 2 / g to 200m 2 / g.
8. A negative electrode plate, characterized in that: Contains the carbonized MOF negative electrode modification material as claimed in claim 7.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 8.